THE ABSTRACTION PROCESS OF NINTH-GRADE STUDENTS IN SOLVING POLYHEDRAL GEOMETRY PROBLEMS BASED ON LEARNING STYLES - Mutiara Amalia Putri; Mubarik Mubarik; Pathuddin Pathuddin; Rahma Nasir (JME (Journal of Mathematics Education), 2026)
This study aims to describe the abstraction process of ninth-grade students in solving polyhedral geometry problems, as viewed from the perspective of learning styles based on the RBC+C model. This study employs a qualitative approach, in the form of a description of the abstraction process of ninth-grade students at SMP Negeri 14 Palu. The research subjects consisted of three ninth-grade students at SMP Negeri 14 Palu who were selected using purposive sampling based on the results of a learning style questionnaire (visual, auditory, and kinesthetic). Data collection began with the distribution of the learning style questionnaire, followed by a written test consisting of polyhedral geometry problems involving cuboids and cubes to measure RBC+C epistemic actions, as well as semi-structured interviews to explore the students’ responses in greater depth. The research findings indicate that all three subjects were able to complete the cognitive activity stages of the RBC+C model, though with varying characteristics and levels of success. Two subjects successfully reached a stable Consolidation stage, while the other subject demonstrated only very limited progress. The dominant thinking barriers occurred during the Building-with stage, taking the form of algebraic misconceptions when reversing formulas and manipulating the notation of mathematical operations. These findings provide insights for educators in understanding the diversity of students’ learning styles and anticipating their cognitive obstacles when designing geometry instruction.